2019
DOI: 10.1627/jpi.62.188
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reversibility on Enhanced Oil Recovery Using Sodium Dodecylbenzene Sulfonate (SDBS)

Abstract: Reduction of interfacial tension (IFT) between residual crude oil and formation fluids in oil reservoirs is the key to enhanced oil recovery (EOR) by surfactant flooding. However, adsorption of injected surfactant on minerals in the oil-bearing rock matrix reduces the effectiveness of this method. The present study investigated the effects of surfactant adsorption and desorption in the rock matrix on the oil recovery ratio achieved by surfactant-EOR. Sodium dodecylbenzene sulfonate (SDBS), a common surfactant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
(10 reference statements)
0
12
0
Order By: Relevance
“…Anionic surfactant possesses a negatively charged polar head that reduces the adsorption onto the Berea sandstone surface. 23 , 24 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anionic surfactant possesses a negatively charged polar head that reduces the adsorption onto the Berea sandstone surface. 23 , 24 …”
Section: Methodsmentioning
confidence: 99%
“…Sodium dodecylbenzene sulfonate (SDBS), an anionic surfactant, was utilized to prepare the base fluid (purchased from Sigma-Aldrich, 99.9% pure, and possesses a molecular weight of 342.4 g/mol). Anionic surfactant possesses a negatively charged polar head that reduces the adsorption onto the Berea sandstone surface. , …”
Section: Methodsmentioning
confidence: 99%
“…If the slug is a surfactant [59], a polymer [60], or even a micellar solution [61], the oil is produced by reduction of IFT or wettability. Major problems associated to surfactant-EOR are the loss of chemical, phase partitioning and trapping, and the slug by passing.…”
Section: Tertiary Oil Recoverymentioning
confidence: 99%
“…Ngo et al reported up to 57.7 mg/100 g-rock of SDBS adsorption on Berea sandstone surface [16]. Ngo et al later added that by increasing salinity from 1 to 3 and 5 wt.% NaCl, the adsorption was doubled that reduced up to 4.6% of oil recovery [17].…”
Section: Introductionmentioning
confidence: 99%